«External Shocks and Political Preferences: Portugal and the economic crisis» - Patrícia Calca; Freire, A. (conferência Crisis and Renewal of Democracy: Portugal in Comparative Perspective, 2008-2019, 2019)
Patricia Calca & André Freire (2019), «External Shocks and Political Preferences: Portugal and the economic crisis», comunicação apresentada na conferência Crisis and Renewal of Democracy: Portugal in Comparative Perspective, 2008-2019, 29-11-2019, ISCTE (Building 2, Auditorium 103), CIES – Linha IV – Observatório da Democracia.